-(x-7y)-2(2y-5x)=0

Simple and best practice solution for -(x-7y)-2(2y-5x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-7y)-2(2y-5x)=0 equation:


Simplifying
-1(x + -7y) + -2(2y + -5x) = 0
(x * -1 + -7y * -1) + -2(2y + -5x) = 0
(-1x + 7y) + -2(2y + -5x) = 0

Reorder the terms:
-1x + 7y + -2(-5x + 2y) = 0
-1x + 7y + (-5x * -2 + 2y * -2) = 0
-1x + 7y + (10x + -4y) = 0

Reorder the terms:
-1x + 10x + 7y + -4y = 0

Combine like terms: -1x + 10x = 9x
9x + 7y + -4y = 0

Combine like terms: 7y + -4y = 3y
9x + 3y = 0

Solving
9x + 3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
9x + 3y + -3y = 0 + -3y

Combine like terms: 3y + -3y = 0
9x + 0 = 0 + -3y
9x = 0 + -3y
Remove the zero:
9x = -3y

Divide each side by '9'.
x = -0.3333333333y

Simplifying
x = -0.3333333333y

See similar equations:

| 3(x+3)-2=3x+2 | | 3x(x^3+6)= | | 20x+25x=180 | | Y=-x+3y | | 3(b+7)=-3 | | -20-2x=30 | | 4756505=2896112+1600x | | 2(x-3)=27 | | 5-4x=4x | | 10n-40=15n+15 | | 3p-3=4(p+1)-p | | 2x+3x-5x+x=42 | | 21=9x+1-5x | | 4(3x-6)=-60 | | 2.5y-(y-5)= | | -30.75m=-73.8 | | 3x+4x+47=180 | | 28=8x+3-3x | | 20x+17=24 | | (2x+x)-3=27 | | y^2-3y=9x | | 3-(7x+4)=15x-4(3-2x) | | X^2+10x=-128 | | 6.3=9.5-0.8x | | 94.20=6.28(x+7) | | X+4+9=3x-2+13 | | 4(ax-c)=bx+3d | | -38.46+3.7a=5.5(1+2.1a) | | 5w^2=-21w-4 | | 9x+y=90 | | 2.6666*5= | | 24=2y-4 |

Equations solver categories